Dietary flavonoid, lignan and antioxidant capacity and risk of hepatocellular carcinoma in the European prospective investigation into cancer and nutrition study - Zamora-Ros, R; González, C; Fedirko, V; Duarte-Salles, T; Jenab, M; Trichopoulou, A; Bamia, C; Lagiou, P; Trichopoulos, D; Trepo, E; Nöthlings, U; Serafini, M; et al. (2013)
Limited epidemiological evidence suggests a protective role for plant foods rich in flavonoids and antioxidants in hepatocellular cancer (HCC) etiology. Our aim was to prospectively investigate the association between dietary intake of flavonoids, lignans and nonenzymatic antioxidant capacity (NEAC) and HCC risk. Data from the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort including 477,206 subjects (29.8% male) recruited from ten Western European countries, was analyzed. Flavonoid, lignan and NEAC intakes were calculated using a compilation of existing food composition databases linked to dietary information from validated dietary questionnaires. Dietary NEAC was based on ferric reducing antioxidant capacity (FRAP) and total radical-trapping antioxidant parameter (TRAP). Hepatitis B/C status was measured in a nested case-control subset. During a mean follow-up of 11-years, 191 incident HCC cases (66.5% men) were identified. Using Cox regression, multivariable adjusted models showed a borderline nonsignificant association of HCC with total flavonoid intake (highest versus lowest tertile, HR=0.65, 95% CI: 0.40-1.04; p=0.065), but not with lignans. Among flavonoid subclasses, flavanols were inversely associated with HCC risk (HR=0.62, 95% CI: 0.39-0.99; p=0.06). Dietary NEAC was inversely associated with HCC (FRAP: HR 0.50, 95% CI: 0.31-0.81; p=0.001; TRAP: HR 0.49, 95% CI: 0.31-0.79; p=0.002), but statistical significance was lost after exclusion of the first 2 years of follow-up. This study suggests that higher intake of dietary flavanols and antioxidants may be associated with a reduced HCC risk. What's new? Coffee, tea, fruits and vegetables, and certain other foods may protect against hepatocellular carcinoma (HCC), thanks to their antioxidant ingredients. This study lends fresh support to that idea, revealing specifically that dietary flavanols, which possess antioxidant activity, could play a favourable role in HCC prevention. Dietary antioxidant capacity from coffee intake in particular was found to be inversely associated with HCC risk, though statistical significance was lost after exclusion of the first two years of follow-up. Assessment of the bioavailability of flavonoids and other antioxidants is needed to confirm links between antioxidant intake and HCC risk. Department, Catalan Institute of Oncology, IDIBELL, Hospital Duran i Reynals, Gran Via 199-203, E-08908 L'Hospitalet de Llobregat, Barcelona, Spain. © 2013 UICC.